help as soon as possible!
![help as soon as possible class=](https://us-static.z-dn.net/files/d5e/7ba58d787055eedc0bc559d4a9efed7e.png)
Answer:
(7-a-x) * (7+a+x)
Step-by-step explanation:
49-2a^x-a^2-x^2
=49-(a^2+2ax+x^2)
=49 - (a+x)^2
=(7-(a+x) * (7+(a+x)
=(7-a-x) * (7+a+x)
Answer:
(7 - a - x)(7 + a + x)
Step-by-step explanation:
(a + x)² = a² + x² + 2ax
Given
49 - 2ax - a² - x² ← factor out - 1 from the last 3 terms
= 49 - (a² + x² + 2ax)
= 49 - (a + x)² ← this is a difference of squares and factors in general as
a² - b² = (a - b)(a + b) , then
49 - (a + x)²
= 7² - (a + x)²
with a = 7 and b = (a + x) , so
= (7 - (a + x) )(7 + (a + x) )
= (7 - a - x)(7 + a + x)